Ekstrak Kafein sebagai Inhibitor Korosi Alami pada Logam Aluminium dalam Media Larutan Asam Sulfat dan Biosolar - Shafara Najla Marinda Sukmawanta; Dyah Ratna Wulan; Kristina Widjajanti; Noor Isnaini Azkiya; Yanty Maryanty (Universitas Andalas, 2022)
This research, the caffeine extract of arabica coffee beans, cacao beans, and black tea leaves will be tested as a corrosion inhibitor on aluminium in an acidic environment and in biodiesel containing acid. This condition resembles the metabolism of microorganisms in biodiesel which produces H2SO4 as one of the causes of corrosion. Arabica coffee, cacao beans and black tea are natural organic ingredients containing caffeine which can inhibit corrosion. In the maceration process used a variable ratio of 70% ethanol solvent with organic matter, namely 225 grams of organic matter with 450 grams of ethanol and 150 grams of organic matter with 450 grams of ethanol. Concentration of caffeine extract from arabika coffee, cacao beans, and black tea leaves was obtained based on HPLC analysis at an effluent rate of 0.8 mL/min. The corrosion inhibition efficiency test on aluminium was observed at 0, 1, 4, 7 and 10 days of immersion. The previously used aluminium has been corroded with 12% H2SO4. The corrosion inhibition efficiency test on aluminium was observed at 0, 1, 4, 7 and 10 days of immersion. The best inhibitor results on aluminium soaked in biosolar containing 12% H2SO4 is tea 1.234,313 ppm with a corrosion rate of 1.6x10-4 g/cm2 day on day 1 to 2.5x10-4 g/ cm2 day on day 10 with an inhibition efficiency of 99%. While the aluminium soaked in H2SO4 12% is tea containing caffeine of 684.373 ppm with a corrosion rate of 1.3 x10-4 g/ cm2 day on day 1 to 3.3x10-4 g/ cm2 day on day 10 with an inhibition efficiency of 64%. The longer the immersion time of aluminium in H2SO4 media with the addition of organic inhibitors, the lower the corrosion rate value because the inhibitors form a layer that protects the aluminium.